Generational Perspectives on Technology's Role in Mental Health Care: A Survey of Adults With Lived Mental Health Experience - Woerner, Molly; Sams, Nichole; Rivera Nales, Cristian; Gorstein, Tara; Johnson, Morgan; Mosser, Brittany A.; Areán, Patricia A. (Frontiers in Digital Health, 2022)
Introduction: Personal technology (e.g., smartphones, wearable health devices) has been leveraged extensively for mental health purposes, with upwards of 20,000 mobile applications on the market today and has been considered an important implementation strategy to overcome barriers many people face in accessing mental health care. The main question yet to be addressed is the role consumers feel technology should play in their care. One underserved demographic often ignored in this discussion are people over the age of 60. The population of adults 60 and older is predicted to double by 2050 signaling a need to address how older adults view technology for their mental health care. Objective: The objective of this study is to better understand why digital mental health tools are not as broadly adopted as predicted, what role people with lived mental health experience feel technology should play in their care and how those results compare across age groups. Method: In a mixed-methods approach, we analyzed results from a one-time cross-sectional survey that included 998 adults aged 18-83 with lived experience of mental health concerns recruited from Prolific, an online research platform. We surveyed participants’ use of technology including their perspectives on using technology in conjunction with their mental health care. We asked participants about their previous use of digital mental health tools, their treatment preferences for mental health care, and the role technology should play in their mental health care. Results: Across all age groups, respondents had favorable views of using digital mental health for managing mental health care. However, older adults rated their acceptability of digital mental health tools lower than middle-aged and younger adults. When asked what role technology should play in mental health care in an open-ended response, most participants responded that technology should play a complementary role in mental health care (723/954, 75.8%). Conclusion: Digital mental health is seen as a valuable care management tool across all age groups, but preferences for its role in care remain largely administrative and supportive. Future development of digital mental health should reflect these preferences.